2020
DOI: 10.3390/toxins12100625
|View full text |Cite
|
Sign up to set email alerts
|

Fumonisin B1 Epigenetically Regulates PTEN Expression and Modulates DNA Damage Checkpoint Regulation in HepG2 Liver Cells

Abstract: Fumonisin B1 (FB1), a Fusarium-produced mycotoxin, is found in various foods and feeds. It is a well-known liver carcinogen in experimental animals; however, its role in genotoxicity is controversial. The current study investigated FB1-triggered changes in the epigenetic regulation of PTEN and determined its effect on DNA damage checkpoint regulation in human liver hepatoma G2 (HepG2) cells. Following treatment with FB1 (IC50: 200 µM; 24 h), the expression of miR-30c, KDM5B, PTEN, H3K4me3, PI3K, AKT, p-ser473-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 81 publications
2
5
0
Order By: Relevance
“…8-OH-DG is a biomarker of oxidative DNA damage, which induces DNA hypomethylation and thus affects cellular stability [ 64 ]. This result is identical to the study by Demirel et al and Arumugam et al [ 65 , 66 ]. In the experiments on rat liver epithelial cell line (Clone 9) and rat kidney proximal tubular epithelial cell line (NRK-52E), FB1 leads to methylation of tumor-related genes (p16, VHL, E-cadherin, and c-myc) [ 65 ].…”
Section: Toxic Mechanism Of Fb1supporting
confidence: 93%
See 1 more Smart Citation
“…8-OH-DG is a biomarker of oxidative DNA damage, which induces DNA hypomethylation and thus affects cellular stability [ 64 ]. This result is identical to the study by Demirel et al and Arumugam et al [ 65 , 66 ]. In the experiments on rat liver epithelial cell line (Clone 9) and rat kidney proximal tubular epithelial cell line (NRK-52E), FB1 leads to methylation of tumor-related genes (p16, VHL, E-cadherin, and c-myc) [ 65 ].…”
Section: Toxic Mechanism Of Fb1supporting
confidence: 93%
“…In the experiments on rat liver epithelial cell line (Clone 9) and rat kidney proximal tubular epithelial cell line (NRK-52E), FB1 leads to methylation of tumor-related genes (p16, VHL, E-cadherin, and c-myc) [65]. Arumugam et al showed that, in HepG2 cells, FB1 suppressed the activity of checkpoint kinase 1 (CHK1) to generate DNA damage by regulating phosphatase and tensin homolog (PTEN), phosphoinositide 3-kinases (PI3K) and protein kinase B (Akt) [66]. This result is similar to that of Yu et al [67].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Reddy et al (2008) showed that PTEN, a major negative regulator of phosphatidylinositol 3-kinase, is a critical regulator controlling oocyte growth and survival. In the present study, the expression levels of PTEN were elevated with increasing mycotoxin content in the diet, and there is evidence that mycotoxins such as FUM B1 [42], OA [43], and DON [44] can regulate PTEN signaling. Results of these studies suggest that mycotoxins might exert their negative effects on follicle survival via PTEN signaling.…”
Section: Discussionsupporting
confidence: 55%
“…[22]. It has speciesspecific toxicity that threatens the health of humans and animals [23]. Pulmonary edema is a unique pathological change due to the action of FB 1 in pigs [24].…”
Section: Discussionmentioning
confidence: 99%